Chitonaster johannae Koehler 1908 - Mah, Christopher L. (Zenodo, 2011)
Chitonaster johannae Koehler, 1908 (Figures 6 A–G) Koehler, 1907: 144; 1908: 542; A.M. Clark, 1993: 250; (as C. johannae Koehler, 1907 ) Distribution. South of South Orkney, South Georgia Islands, and Elephant Islands, 2856–4204 m. Distinctions from other species. Chitonaster johannae is herein restricted to those Chitonaster with valvate pedicellariae, abactinal arm plates in transverse series, with clustered spines on abactinal and superomarginal spines with relatively small abactinal plates, and lacking papulae. All C. johannae examined with these characters, including Koehler’s (1908) original description are apparently restricted to abyssal depths (> 2856 m). Shallowwater specimens, including those referred to C. johannae by Mein (1992) and Stampanato and Jangoux (1993), are referred to C. trangae n. sp. Comments on type material. MNHN EcAh 3511 is herein designated as the lectotype from Koehler’s (1908) syntype series. It corresponds in nearly ever regard to one specimen, with R=23.0 mm, indicated in Koehler’s (1908) full description and designation of this species. This lot included a tag reading “ Scotia ”, the collecting vessel. Other members of Koehler’s syntype series could not be located in the Paris collections and it is unclear how many of the syntypes remain extant. EcAh 3511 is the functional holotype for this species. Material examined. MNHN EcAh 3511, 62º10’S, 41º20’W, 3246 m (=1775 fms). Coll. Scotia 18 March 1903 (1 wet spec. R= 2.3 cm, r= 1.1); USNM 1086359 66˚ 23 S, 45˚ 49 W to 66˚ 20 S, 45˚ 52W, 4200–4204 m. Coll. U. Southern California. (1 dry spec. R=2.5, r=1.1); USNM 1018953 South of South Orkney Islands, Weddell Sea. 63˚21’S, 44˚51’W to 63˚28’S, 44˚57’W, 3587–3660 m. coll. US Antarctic Research Program. (1 dry spec. R=2.3, r=1.1); USNM E13501. South of South Georgia, South Atlantic Ocean. 56˚53’ S, 37˚33’W, 3138–3144.0 m. Coll. R/V Eltanin (2 dry specs.R=2.9, r=1.2; R=3.3, r=1.3). E 13502, SE of South Orkney Islands, Antarctica. 62˚05 S, 40˚44’W. 3250–3285.0 m. Coll. R/V Eltanin (1 ...